Thermoresponsive polymer gated and superparamagnetic nanoparticle embedded hollow mesoporous silica nanoparticles as smart multifunctional nanocarrier for targeted and controlled delivery of doxorubicin. (18th August 2020) - Asghar, Khushnuma; Qasim, Mohd; Dharmapuri, Gangappa; Das, Dibakar
Abstract: The design and development of drug-delivery nanocarriers with high loading capacity, excellent biocompatibility, targeting ability and controllability have been the ultimate goal of the biomedical research community. In this work, we have reported the synthesis and characterization of novel and smart thermoresponsive polymer coated and Fe3 O4 embedded hollow mesoporous silica (HmSiO2 ) based multifunctional superparamagnetic nanocarriers for the delivery of doxorubicin (Dox) for cancer treatment. P(NIPAM-MAm) coated and Fe3 O4 nanoparticle (NP) embedded hollow mesoporous silica nanocomposite (HmSiO2 -F-P(NIPAM-MAm)) was prepared by the in situ polymer ization of NIPAM and MAm monomers on the surface of hollow mesoporous silica NPs (HmSiO2 ) in the presence of Fe3 O4 NPs, oxidizer and crosslinker. TEM analysis showed nearly spherical morphology of HmSiO2 -F-P(NIPAM-MAm) nanocarrier with a diameter in the range of 100–300 nm. The coating of P(NIPAM-MAm) layer and embedding of Fe3 O4 NPs on the surface of the HmSiO2 NPs was revealed by HRTEM analysis. XRD and FTIR analysis also confirmed the presence of P(NIPAM-MAm) shells and Fe3 O4 NPs on hollow mesoporous silica NPs. VSM analysis suggested the superparamagnetic nature of HmSiO2 -F-P(NIPAM-MAm) nanocarrier. DSC analysis of HmSiO2 -F-P(NIPAM-MAm) nanocarrier showed a phase transition at the temperature of ∼38 °C. The prepared HmSiO2 -F-P(NIPAM-MAm) nanocarrier was investigated for its suitability for drug-delivery application using doxorubicin as the model drug by an in vitro method. The encapsulation efficiency and encapsulation capacity were found to be 95% and 6.8%, respectively. HmSiO2 -F-P(NIPAM-MAm)-Dox has shown a pH and temperature-dependent Dox release profile. A relatively faster release of Dox from the nanocarrier was observed at temperature above the lower critical solution temperature (LCST) than below the LCST. HmSiO2 -F-P(NIPAM-MAm) nanocarrier was found to be biocompatible in nature. In vitro cytotoxicity studies against Hela cells suggested that the HmSiO2 -F-P(NIPAM-MAm)-Dox nanocomposite nanocarrier has good anticancer activity. In vitro cellular uptake study of HmSiO2 -F-P(NIPAM-MAm)-Dox nanocomposite nanocarrier demonstrated its good internalisation ability into Hela cells. Thus, the prepared nanocomposites show potential as nanocarrier for targeted and controlled drug delivery for cancer treatment.